Location privacy protection for mobile social network - Zhi-kai XU; Hong-li ZHANG; Jian-tao SHI; Zhi-hong TIAN (网络与信息安全学报)
Given its high utility value,mobile social network services(MSNS),however,has raised serious concerns about users’ location privacy.The location privacy requirements of users in MSNS are personal and dynamic,thus a metric called confidence was proposed to quantify the privacy risks.To avoid the adversary inferring users’ privacy,a method of legation privacy protection was designed to calculate the correlation between the locations through lo-cation information,social relation and personal information.Then the correlation and the space-time background were used to evaluate whether the users’ published geo-content meet the user’s privacy requirement.Eventually,our experimental results demonstrate the validity and practicality of the proposed strategy.